2020
DOI: 10.2478/jas-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Behavior of Honeybees (Apis Mellifera L.) and Ground Bumblebees (Bombus Terrestris L.) and its Influence on Seed Yield and Oil Quality of Oil Tree Peony Cultivar ‘Fengdan’ (Paeonia Ostii T. Hong et J. X. Zhang)

Abstract: AbstractOil peony (Paeonia spp.) is a new type of woody oil crop in China with a large cultivation area. Inadequate pollination is one of the main reasons for low seed yield. A pollination net room was built at an oil tree peony base, the numbers of honeybees (Apis mellifera L.) and ground bumblebees (Bombus terrestris L.) were artificially increased and the foraging behaviors and daily activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In the current study, bee pollination most prominently enhanced the seed quantity, leading to heavier seeds, increased oil content, and decreased seed deformity rate. But it had no significant effect on the content of UFA in seed oil, which was the same as the results of He et al (2020) [38]. Whether other oil quality parameters and seed nutritional values are similarly affected by the pollination mode demands further investigation for crops and quality measures.…”
Section: Plos Onesupporting
confidence: 85%
See 4 more Smart Citations
“…In the current study, bee pollination most prominently enhanced the seed quantity, leading to heavier seeds, increased oil content, and decreased seed deformity rate. But it had no significant effect on the content of UFA in seed oil, which was the same as the results of He et al (2020) [38]. Whether other oil quality parameters and seed nutritional values are similarly affected by the pollination mode demands further investigation for crops and quality measures.…”
Section: Plos Onesupporting
confidence: 85%
“…For this reason, we set up a pollinator control net room supplemented with bees to evaluate pollination deficit in oil tree peony field. Previous studies have shown that A. mellifera are more efficient pollinators than Bombus terrestris on oil tree peony, and that pollination by A. mellifera can accelerate fruit development rates and yield [37,38]. This study compared the effects of different pollinator colony densities on the fruit development rate and fruit yield of oil tree peony, and provided theoretical support for further utilization of pollinator bee resources in oil tree peony field and high yield and high benefit of oil tree peony.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations